(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: collocability, syntagmatic macrocomponent, selective microcomponent, connotation, components of connotation, expressiveness, evaluation, intensity, stylistic reference. The article is devoted to the connotative-syntagmatic analysis - one of the methods of linguistic research that has been worked out for the purpose of detection and restrictions on compatibility in expressive words (with connotation value). The essence of this analysis consists in identification of compatible components of connotation (expressiveness, emotionality, evaluation, intensity, stylistic reference), which allow and forbid compatibility of the given word with other words. Vlavatskaya Marina Vitalievna - candidate of linguistics, professor assistant.